High Gamma and Beta Temporal Interference Stimulation in the Human Motor Cortex Improves Motor Functions - Ma, Ru; Xia, Xinzhao; Zhang, Wei; Lu, Zhuo; Wu, Qianying; Cui, Jiangtian; Song, Hongwen; Fan, Chuan; Chen, Xueli; Zha, Rujing; Wei, Junjie; Ji, Gong-Jun; et al. (Frontiers in Neuroscience, 2022)
Background: Temporal interference (TI) stimulation is a new technique of noninvasive brain stimulation. Envelope-modulated waveforms with two high-frequency carriers can activate neurons in target brain regions without stimulating the overlying cortex, which has been validated in mouse brains. However, whether TI stimulation can work on the human brain has not been elucidated. Objective: To assess the effectiveness of the envelope-modulated waveform of TI stimulation on the human primary motor cortex (M1). Methods: Participants attended three sessions of 30-min TI stimulation during a random reaction time task (RRTT) or a serial reaction time task (SRTT). Motor cortex excitability was measured before and after TI stimulation. Results: In the RRTT experiment, only 70 Hz TI stimulation had a promoting effect on the reaction time (RT) performance and excitability of the motor cortex compared to sham stimulation. Meanwhile, compared with the sham condition, only 20 Hz TI stimulation significantly facilitated motor learning in the SRTT experiment, which was significantly positively correlated with the increase in motor evoked potential. Conclusion: These results indicate that the envelope-modulated waveform of TI stimulation has a significant promoting effect on human motor functions, experimentally suggesting the effectiveness of TI stimulation in humans for the first time and paving the way for further explorations.